The great British baking show. Season 1 [videorecording (DVD)] - Berry, Mary, 1935-; Hollywood, Paul (PBS, 2017)
Follow the trials and tribulations of passionate amateur bakers whose goal is to be named the U.K.'s best. Each week, the bakers tackle a different skill, the difficulty of which increases as the competition unfolds, judged by Mary Berry and Paul Hollywood.